KEBIJAKAN KETAHANAN PANGAN DI INDONESIA MELALUI PENDEKATAN ANALISIS BIBLIOMETRIC - Maulana, Delly; Habibi, Fikri; Purnama, Indra Nizar (Jurnal Ilmu Sosial dan Ilmu Politik (JISIP), 2024)
The issue of food security is currently a high priority because making a country without poverty and without hunger is one of the goals of the Sustainable Development Goals (SDGs). Therefore, there needs to be a strategic policy in realizing it. This paper tries to reveal the mapping of research related to food security policy using bibliometric analysis so that it can provide an overview of best practices in addressing the issue. The method used in this research is a literature review study using bibliometric analysis using VosViewer software. The results of the study illustrate the development of food security policy research from year to year with the most issues being social society. While issues that are still rarely studied are food security policies related to land, environmental degradation, food security for households, groundwater use, and public health aspects.Â  Furthermore, there are several policy strategies to resolve food security issues in Indonesia, namely:Â  First, the government must make agricultural policies that encourage collaboration between stakeholders, namely the government, companies, farmers, and scientists; Second, there needs to be a policy that encourages the transformation of food technology to create food security, Third, there needs to be a policy to empower people to return to agricultural land, Fourth, there needs to be a policy to overcome agricultural land problems, and Fifth, there needs to be a policy to control food waste.